Analysis of Temporary Preloading for Bridge Approach Embankment to Eliminate Secondary Compression Case Study: Probolinggo – Banyuwangi Toll Road Construction Project Section 3 STA 40+550 - Muhammad Rizal Permadi; Indrasurya B. Mochtar; Noor Endah Mochtar; Reza Kazhimi (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2025)
Probolinggo - Banyuwangi Toll Road is part of the National Strategic Project, has a length of 172 km which is divided into 7 sections. One of the challenges faced is soft soil, where information is obtained in section 3 precisely STA 40 + 550 there is soft soil, which has low bearing capacity and high compressibility. The depth of the soft soil itself reaches 10 meters, with the plan to build in the approach bridge area which has a 10 meter high embankment. Considering the high embankment, based on previous studies, it is estimated that the amount of primary and secondary compression generated is quite large. This study analyzes primary, and secondary compression in bridge approach embankments built on soft soil, focusing on eliminating secondary compression using the preloading method, while the primary compression time is accelerated using Prefabricated Vertical Drains (PVD). Primary consolidation results in a 1.35-meter settlement, and secondary settlements vary over 20 years. From the analysis, it is found that the annual rate of secondary settlements decreases after year 10, so it is considered that the year 10 settlements are eliminated. To eliminate these settlements at year 10 of the operational period, the required embankment height increases by up to 13.60 meters of granular backfill, preloading of 4.49 t/m2 is equivalent to 2.26 m, and the height of the embankment to be demolished is 1.85 m.